CLOTHING CONSUMPTION AND DISPOSAL PATTERN AMONGST COLLEGE GOING GIRLS: AN EXPOLORATRY STUDY - Singh, Shikha; Kajal; Aggarwal, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For the textile industry to be considered sustainable its environmental impact needs to be reduced by 30-100% by using multiple measures like reusing and recycling. This study sought to determine how conscious college girls between the age of 18 and 22 are of the environmental effects of mindless clothing consumption and disposal. This study examined a number of distinct constructs such as environmental concern, environmental influence on clothing consumption and disposal, consumer behavior in relation to clothing, reasons for buying clothes, clothing disposal pattern, and barriers to clothing disposal for college-going girls. Both qualitative and quantitative analyses were employed to accomplish the goals. Six focus groups with ten to twelve college-age girls each were held as part of the qualitative study. The results of the focus group conversations were used to build a structured questionnaire with a 5-point Likert scale. The questionnaire was administered to 201 college going girls aged 18 to 22. Thus, gathered data was analyzed descriptively as well as statistically using SPSS. Reliability of each scale was checked using Cronbach’s alpha method. To identify the factors in each variable, Principal Component Analysis was used. The survey discovered that while respondents were aware of environmental issues, they were unaware of how the production and disposal of garments affected the environment. The respondents were aware of a variety of recycling and reusing practices; however, they do not engage in these practices. This can be the case because another family member handles these tasks. They frequently buy new clothes in order to keep up with fashion trends and gain psychological comfort. People are unaware of the environmental impact of their clothing disposal, consumption, and purchasing.